Covid-19 pandemic: improving health with proper self-medication and the use of medicinal plants - Pinasti Utami; Muhammad Thesa Ghozali; Nurul Maziyyah; Salmah Orbayinah; Surria Dwiwahyu (Universitas Muhammadiyah Magelang, 2022)
The Covid-19 pandemic has an effect on people's drug-self-medication behavior. However, community knowledge about the use of self-medication is still lacking. This is also consistent with public perception of TOGA (Family Drugs Plant). For this reason, the devotees make a community service program to socialize the importance of TOGA and provide training in making TOGA. This activity is being carried out in collaboration with the Institute for Environment and Disaster Management of the Aisyiyah Region Special Region of Yogyakarta (LLHPB PWA DIY), which focuses on environmental issues, and in collaboration with Aisyiah community in Umbulharjo, which is working to mobilize the potential of women in order to form Aisyiah cadres. This activity includes three programs: the formation of a progressive Youth Health Team, health training related to drug self-medication and health promotion, and workshops on the use of vacant land to increase food security. Training and workshops can increase the knowledge of cadres, both related to self-medication and the environment. In addition, the topic of using medicinal plants for disease prevention and immune enhancement is a new issue in the community.